A descriptive study of the prenatal services under the privileged mother's services program of a Metro Cebu Hospital - Aguilar, Elmira Judy T. (Animo Repository, 1997)
The study was conducted in a tertiary, private hospital in Metro Cebu. Its aim is to describe the prenatal services of the Privileged Mother's Services (PMS) on the areas of its services, policies, profile of the providers and the clients. All the medical staff and thirty prenatal clients were interviewed and observed.The findings reveal that the cost is the main reason for the enrollment of women aside from the perceived better services it offers compared to the other hospitals. However, there are existing policies which discourage women from continuing their maternal health care such as the compulsory blood donation. Family planning services and tetanus toxoid administration are not offered because the hospital espouses a pro-life policy. The other policies which are advantageous include mandatory breastfeeding, minimum age of gestation when prenatal care should begin, and minimum number of prenatal visits, among others.The entire PMS program helps in making health care affordable to women. However, the quality of care aspect of PMS must be assessed. Thus, an instrument should be developed to evaluate the wide array of services it offers. Ultimately, the level of its quality of care would benefit the women whom it purports to serve by providing services that are within the acceptable standards of maternal health care.